PEMBERDAYAAN MASYARAKAT DESA CERME DENGAN BUDIDAYA TANAMAN BAWANG DAYAK SEBAGAI MINUMAN HERBAL - Fatichatur Rachmaniyah; Siti Shoimah; Latif Maulana; Ahmad Jemy; Nur Faidzin; Khoirul Umam (Jurnal Pengabdian kepada Masyarakat, 2023)
Dayak onion (Eleutherine americana Merr) is a native South American plant which is also found growing in Java, Kalimantan. Local residents in Kalimantan have used this Dayak Onion as a traditional medicine. The part that can be utilized in this plant is the tuber. The purpose of this activity is to increase public village Cerme knowledge, about the efficacy and benefits of the Dayakonion plant as a family medicinal plant, the use of the land for the house and the Dayak onion business as a home industry for Dayak onion wedang to increase family income in improving the welfare of the community, especially PKK (Building Family Wellbeing) of Cerme Village in Ngimbang District,Lamongan Regency.